Mobile RNAs—the magical elf traveling between plant and the associated organisms - Shuo Zhang; Zhi Hong (ExRNA)
Abstract RNA interfering (RNAi) is mediated by small non-coding RNAs (sRNAs) and efficiently silence gene expression at the posttranscriptional level in eukaryotes. In addition to functioning within a cell, such silencing RNA signals can also be transmitted over a long distance or even cross-species, therefore named mobile RNAs. Recent studies have demonstrated that mobile RNAs have the potential to suppress interspecies gene expression when plants suffer from biotic stress. In this review, we discuss the role of mobile RNAs as silencing signals transmitted between host plants and fungi, parasitic plants, and mammals. The potential applications of mobile RNAs on plant protection to resist the pests and pathogens by bioengineering strategy are also prospected.